What’s New About the “New Public Health”? - Awofeso, Niyi (© American Journal of Public Health 2004, 2004)
From its origins, when public health was integral to societies’ social structures, through the sanitary movement and contagion eras, when it evolved as a separate discipline, to the “new public health” era, when health promotion projects like Healthy Cities appear to be steering the discipline back to society’s social structure, public health seems to have come full circle. It is this observation that has led some to ask, “What’s new about the ‘new public health’?” This article addresses the question by highlighting what is new about the health promotion era—including adapted components of previous eras that have been incorporated into its core activities—and its suitability in addressing established and emerging public health threats.